Child Development Workers (CDWs)' Challenges and Experiences on Supplementary Feeding Program (SFP) in the Child Development Centers (CDCs) of Vintar, Ilocos Norte - Kyle Vincent M. Gaoiran; Jeremy Adrian D. Guiang (Future Science / FSH-PH Publications, 2026)
Despite recognizing the importance of the SFP in addressing early childhood malnutrition, limited literature has been documented on the lived challenges and experiences of Child Development Workers (CDWs) especially in rural child development centers (CDCs). This paper aims to explore the challenges and experiences faced by CDWs when carrying out SFP within the CDCs of Vintar, Ilocos Norte. A qualitative-descriptive approach was used wherein 42 respondents comprising CDWs from five zones of the municipality were interviewed using a semi-structured interview guide via focus group discussions (FGDs). The qualitative data obtained was then subjected to thematic analysis according to Braun and Clarke. Results reveal that the challenges and experiences can be described under two major categories: (1) implementation challenges and (2) implementation experiences. The first category includes health management issues, resource issues, and operational issues while the second category highlights healthy experiences in terms of health and nutrition management, process and procedure in program delivery, and beneficial program outcomes. It is concluded that CDWs play a vital frontline role which involves not only food but also health supervision, cooperation and planning. Effective coordination between barangays and LGUs, proper guidance in the execution of procedures, flexible budget, and strong community participation are key to sustaining the program.